Vietglish: translanguaging in Vietnamese and English - Nguyen, B-LL (2021)
This dissertation investigates the translanguaging patterns of five Vietnamese-American individuals residing in the state of California, focusing on the attitudes, motivations, and insights of these participants on their use of Vietnamese as a heritage language. Since the beginning of large-scale immigration from Vietnam to the United States following the sociopolitical events of the 1970s, overseas Vietnamese communities have had extensive contact with the language and culture of the new host countries to which they had emigrated. This study specifically investigates the translanguaging practice of combining Vietnamese and English within conversations and utterances for daily, vernacular use, informally dubbed “Vietglish”.